112 hormonal supplementation strategies for improvement of pregnancy rates in embryo transfer in alpacas - Vivanco-Mackie, H. W. (2017)
The aim was to improve the pregnancy rate in recipient alpacas following embryo transfer. Two experiments were carried out, Experiment 1 in the southern highlands (4,100 m elevation) and Experiment 2 (E2) in the central highlands (3,200 m elevation) of the Peruvian Andes. In both experiments, a group of alpaca donors was subjected to superovulation and embryo flushing as per procedures already described (Vivanco 2013 29th Annu. Mtg. European Embryo Transfer Association, 43–74). The synchronization of the recipient alpacas and ovulation induction in both experiments was made by ultrasonography selection of the alpacas with follicles greater than 8 mm and their exposure to vasectomized males followed by an injection of GnRH (0.0042 mg of acetate of buserelin, Buserelina Zoovet®, Laboratorio Zoovet, Santa Fe, Argentina). The embryo transfers in both locations were made by laparoscopically aided laparotomy 6.5 days after ovulation induction. In Experiment 1, 29 recipient alpacas were distributed in 2 treatments: treatment 1 (n = 14) was the control (no hormonal supplementation); alpacas in treatment 2 (n = 15) received an injection of 300 IU of eCG (Novormon®, Partnar Animal Health, Port Huron, MI, USA) and the insertion of an intravaginal sponge containing 60 mg of medroxyprogesterone acetate (Progespon®, Syntex SA, Buenos Aires, Argentina) 72 h after the injection of the GnRH applied at ovulation induction, the sponges remained in the vagina of the recipients up until Day 21 post-transfer. In Experiment 2, ten recipient alpacas were distributed into 2 treatments, treatment 1 as the control (n = 5, no hormonal supplementation) and treatment 2 (n = 5) in which the recipient alpacas received a dose of a nonsteroidal anti-inflammatory (2 mg/kg of tolfenamic acid, Tolfén L.A. 8%®, Agrovet Market Animal Health, Lima, Peru) 12 h before the embryo transfer with the aim of blocking PGF2α secretion and preventing corpus luteum (CL) regression. At time of transfer, control recipients in Experiment 1 showed in average 0.71 ± 0.71 follicles and 1.14 ± 0.53 CL and the treatment 2 recipients showed 2.73 ± 2.52 follicles and 1.20 ± 0.56 CL, respectively, and there was no significant differences (P > 0.05) between treatment groups in the pregnancy rates 60 days post-transfer, being 35.7% (5/14) and 26.7% (4/15) for treatment 1 (control) and 2 (hormonally supplemented), respectively. In Experiment 2, the number of follicles and CL were not recorded; the differences between treatments for pregnancy rates were also nonsignificant (P > 0.05), the pregnancy rates were 20% (1/5) and 40% (2/5) for treatment 1 (control) and treatment 2 (injected with anti-inflammatory) respectively. In the first experiment, the hormonal treatment increased the number of non-ovulatory follicles; this could have negatively influenced its effectivity on increasing pregnancy rates. In the second experiment, a tendency can be observed for better holding rates in alpacas receiving the anti-inflammatory treatment; it will be necessary to increase the number of observations in a new experiment in order to determine if this will have a significant effect on improving holding rates in alpacas.